2014
DOI: 10.4236/ojped.2014.44041
|View full text |Cite
|
Sign up to set email alerts
|

Study of Vision Problems in Schools in Libreville and Owendo, Gabon

Abstract: The purpose of this work is to evaluate the epidemiological aspects of vision problems and their repercussions in the schooling of children in Libreville and Owendo. Methodology: This transversal and descriptive study was carried out in May and June 2011. Included in the study were children in the 7 th and 8 th grades of the primary schools in Libreville and Owendo. For each child, an eye exam, including the subjective measure of visual acuity, was carried out using the Monoyer scale, and the color vision asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…7,20 A study in Gabon which is in West Africa as Nigeria found a very high prevalence of colour vision defect (15.5%). 21 Their reason for this high prevalence was due to some false positive readings which may be due to poor comprehension and reading of Ishihara chart by some students. Deutan defect (54.5%) was the commonest colour vision defect found in this survey.…”
Section: Discussionmentioning
confidence: 99%
“…7,20 A study in Gabon which is in West Africa as Nigeria found a very high prevalence of colour vision defect (15.5%). 21 Their reason for this high prevalence was due to some false positive readings which may be due to poor comprehension and reading of Ishihara chart by some students. Deutan defect (54.5%) was the commonest colour vision defect found in this survey.…”
Section: Discussionmentioning
confidence: 99%
“…Lower rates (1.7%) were reported in 2009 by the pilot study in FNSI schools in Cotonou [20] and Burkina-Faso (2.3%) [13]. Higher values were reported respectively 15% in Cotonou by Latour, et al [5], 9% in Marrakech [10], 8.7% in Rabat [21], 12.4% in Cameroon [15] and 10.8% in Libreville [22]. The differences noted between the rates found could be related to the sample size as ours was relatively smaller.…”
Section: Overweight and Obesitymentioning
confidence: 93%
“…Sweets were regularly purchased at school by 27.5% of the children. Ategbo, et al reported a higher prevalence of sugar consumption, up to 88.4% [22]. This difference may be due to the availability and affordability of sweetened drinks within the vicinity of the schools.…”
Section: Factors Associated With Overweightmentioning
confidence: 97%
“…The health systems in these countries have a pyramidal structure comprising three levels (primary, secondary and tertiary). [38][39][40] The primary level represents the operational unit of the health pyramid and is located in each health district to provide basic eye care and ensure hygiene education and awareness.…”
Section: Study Design and Frameworkmentioning
confidence: 99%